CONSUMER BEHAVIOR STUDY ON THE ACCEPTANCE OF AIRBNB FROM CONSUMER IN SURABAYA, INDONESIA - Felicia Alamanda Wahono; Endo Wijaya Kartika (Jurnal Hospitality dan Manajemen Jasa, 2017)
The overall aim of this study is to investigate the acceptance of Airbnb accommodation establishments from people belonging to the Millennials Generation in Surabaya, Indonesia. The study employed an online survey, in the form of a questionnaire to implement its fieldwork and to get hold of the respondents’ views. The key findings of the fieldwork addressed that there are three main factors which affect the Millennials when selecting an Airbnb accommodation and those are price, amenities, and consumer reviews. Additionally, safety, cleanliness, and hosts’ attitudes are also important factor for the acceptance of Airbnb in Indonesia.